Holistic Approaches to Religious Education Management in Madrasah Aliyah Negeri - Mappasanda, Rante; Thaha, Hisban; Guntur, Muhammad (International Journal of Asian Education, 2025)
Religious education plays a fundamental role in shaping students’ moral and spiritual values, especially in Madrasah Aliyah Negeri, which integrates both general and religious education. This study explores holistic approaches to religious education management, focusing on strategic planning, implementation, evaluation, and community participation. A qualitative research approach using a case study method was employed, involving interviews, observations, and document analysis to assess the effectiveness of religious education management. The findings indicate that effective religious education requires a combination of a well-structured curriculum, extracurricular activities, community involvement, and the use of technology. The main challenges in managing religious education include resource limitations, a lack of educators proficient in modern pedagogical methods, and external influences from social environments and digital media. To address these challenges, schools must develop teacher training programs, strengthen collaboration with parents and communities, and integrate technology as a learning tool. This study emphasizes the importance of continuous evaluation to ensure that religious education is theoretical and contributes to students’ character formation and behavior. By adopting a holistic management approach, Madrasah Aliyah Negeri can enhance the effectiveness of religious education, strengthen students’ religious identity, and prepare them to navigate modern challenges with strong moral foundations.